2020
DOI: 10.4049/immunohorizons.2000055
|View full text |Cite
|
Sign up to set email alerts
|

Tonic TCR Signaling Inversely Regulates the Basal Metabolism of CD4+ T Cells

Abstract: The contribution of self-peptide-MHC signaling in CD4 + T cells to metabolic programming has not been definitively established. In this study, we employed LLO118 and LLO56, two TCRtg CD4 + T cells that recognize the same Listeria epitope. We previously have shown that LLO56 T cells are highly self-reactive and respond poorly in a primary infection, whereas LLO118 cells, which are less selfreactive, respond well during primary infection. We performed metabolic profiling and found that naive LLO118 had a dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…After positive selection, mature CD4 + T cells exit the thymus and circulate in the periphery where they survey pMHC, which, in the absence of an immune challenge, will be occupied by self-peptide. Tonic signaling does not propagate canonical T cell activation; yet, these weaker TCR interactions still affect basal signaling, gene expression, and metabolic activity 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 . Multiple markers (including CD5 24 and Nur77 25 , 26 ) have informed us of a broad spectrum of tonic signaling strengths experienced by the diverse repertoire of TCRs in a polyclonal population, and recent work suggests tonic signaling may be responsible for discretely tuning individual CD4 + T cell responses to foreign antigen 15 , 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…After positive selection, mature CD4 + T cells exit the thymus and circulate in the periphery where they survey pMHC, which, in the absence of an immune challenge, will be occupied by self-peptide. Tonic signaling does not propagate canonical T cell activation; yet, these weaker TCR interactions still affect basal signaling, gene expression, and metabolic activity 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 . Multiple markers (including CD5 24 and Nur77 25 , 26 ) have informed us of a broad spectrum of tonic signaling strengths experienced by the diverse repertoire of TCRs in a polyclonal population, and recent work suggests tonic signaling may be responsible for discretely tuning individual CD4 + T cell responses to foreign antigen 15 , 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of noncognate-antigen:HLA-DR complexes on APCs by the TCR, albeit incapable of driving full T cell activation, generates nuanced effects on T cell activation and gene expression 40, 41 . We posited that homotypic T-T cell interactions through non-cognate HLA-DR:TCR contacts could control TLR4 expression on T cells.…”
Section: Resultsmentioning
confidence: 99%
“…We have broadened the range of molecules involved in homotypic T:T cell interactions by identifying that they can be additionally established through non-cognate HLA-DR:TCR interactions. Non-cognate HLA-DR:TCR interactions between APCs and T cells are known to alter T cell genetic profile 40, 41 . Thus, it is possible that homotypic T-T cell interactions through non-cognate HLA-DR:TCR contacts might drive TLR4 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the mechanism behind this enhanced proliferation revealed greater responsiveness to inflammatory cues but not enhanced antigenic pMHC binding (142). Further associations of tonic signaling and CD5 expression have been found with other features involved in T cell responsiveness, including expression of the phosphatases CD45 and PTPN2 (143,144) and metabolic state (145). Moreover, a study in naïve CD4 + T cells demonstrated CD5associated differences in chromatin accessibility (146), suggesting that self-pMHC signaling can cause long-lived reprogramming in naïve T cells.…”
Section: Origins Of Heterogeneity Among Naïve T Cellsmentioning
confidence: 94%